Developing Government Bond Markets : A Handbook. (Manuals and Guides, 2001)
This handbook is a comprehensive and authoritative reference for both senior policymakers-those responsible for the development of government bond markets in their own countries-and all individuals responsible for guiding the market development process at the operational level-those who have a substantial need to understand the policy issues involved.